The political writings of Samuel Pufendorf - Pufendorf, Samuel, Freiherr von, 1632-1694 (Oxford University Press, 1994)
The seventeenth-century philosopher Samuel Pufendorf was one of the most widely read natural lawyers of the pre-Kantian era. This volume presents the basic arguments and fundamental themes of his political and moral thought. Selections from the texts of Pufendorf's two major works, Elements of Universal Jurisprudence and The Law of Nature and Nations, have been brought together to make Pufendorf's moral and political thought more accessible. The selections appear here in a new English translation which far exceeds what is currently available. The translator has constructed a rendering of the Latin that is sophisticated but clear, and the volume has been prepared with an emphasis on continuity and readability. The editor has included a substantive introduction intended to acquaint readers with Pufendorf and his political thought and to indicate why his work has relevance for contemporary political discourse.